Fragment of a lintel to the south of Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
View of a fragment of a lintel found to the south of the main Neelkanth Mahadev Temple. The lintel has friezes with deities depicted on it.